Implementasi Terapi Bermain (Play Dough) pada Anak Pre-School yang Menjalani Perawatan Hospitalisasi dengan Masalah Keperawatan Ansietas: Studi Kasus - Musviro Musviro; Pita Nurparamitha Bahari; Sri Wahyuningsih; Nurul Hayati; Rizeki Dwi Fibriansari (KHD Production, 2023)
Hospitalization is one of the causes of trauma and psychological trauma in children who are hospitalized. One of the impacts that often occurs in children undergoing hospitalization is anxiety. The aim of this research is to provide nursing care for children undergoing treatment in hospitals with anxiety problems using a playdough approach in the Bougenville Room at RSUD Dr. Haryoto Lumajang. Data collection used was interviews, observation, and documentation study of the anxiety experienced by patients. Research shows that play therapy using playdough is carried out for 15 to 30 minutes once a day makes children more interested and follow directions in playing so that they can divert their anxiety while they are in the hospital. This play therapy medium is effectively used to reduce anxiety in children when the child is in the hospital. Jam is a play therapy medium that is also useful for stimulating children's motor development because, in this play dough game, the way of playing uses the five senses, so it is effective as a learning medium given by parents to children.